Hard Work: The Making of Labor History - Palmer, Bryan D. (Relations industrielles / Industrial Relations, 2001)
Hard Work: The Making of Labor History, by Melvyn Dubofsky, is reviewed.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; History; Labor Unions; Labor force; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Social classes